ANALISIS DAMPAK PAJAK E-COMMERCE, INFRASTRUKTUR DIGITAL, DAN SKALA USAHA TERHADAP KEPATUHAN PAJAK UMKM DI JAWA BARAT - Abdurrosyid, Moh. (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2025)
This study seeks to analyze the influence of e-commerce tax, digital infrastructure, and business scale on the tax compliance of Micro, Small, and Medium Enterprises (MSMEs) in West Java. The research employs the quantitative method with data collected from a structured questionnaire bearing a Likert scale (1–5) from 220 MSME respondents. SEM-PLS 3 was applied in data analysis. The three independent variables, e-commerce tax, digital infrastructure, and business scale, all have positive and significant effects on tax compliance, finds the study. Among them, digital infrastructure was found to be the most important driver, followed by business size and tax policy on e-commerce. The results highlight the imperative for facilitative digital tools, transparent tax policies, and size-based support to enable improved compliance in the digital economy. The study makes viable contributions to policymakers and stakeholders in tax policy efficiency and promoting MSME inclusion in the formal sector.